8 Guide steps for setting up a Climate-Smart Village in South east Asia (Multi-language) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
The guide is available and already disseminated to the local stakeholders, particularly the members of ASEAN Climate Resilience Network. The guide is also translated into the major languages in Southeast Asia (Bahasa Indonesia, Bahasa Malayo, Burmese, Filipino, Khmer, Laotian, Thai, and Vietnamese).